Laser Welding of Complex Phase and Dual Phase Advanced High Strength Steels - The Effects that Welding has on Microstructure and Formability - Martin-Root, Christopher Kenneth Haines (University of Waterloo, 2020)
To assist in the successful applications of tailor-welded assemblies made from advanced high strength steel (AHSS), there needs to be a thorough understanding of how laser welding process parameters influences the weld cross-section profile, mechanical properties, global formability and local formability performance of the base metal. This study investigates microstructure formability correlation of fiber laser welds of an un-coated complex phase (CP) AHSS and a hot dipped galvannealed (HDGA) dual phase (DP) AHSS. Both steels were developed to have a minimum tensile strength of 980 MPa, a minimum yield strength of 590 MPa and a minimum total elongation of 12% in the material’s transverse direction - 90° to the material’s rolling direction. Tensile tests, limiting dome height (LDH) tests, bi-axial stretch tests, forming-strain analyses, and hole expansion tests (HET) were used to compare base metal (BM) samples to laser welded samples. The LDH and bi-axial stretch tests showed that, for both materials, the global formability of the welded samples was lower than that of the base metal. For the CP 980 steel, observations during global formability were correlated to the martensitic dominant regions within the weld’s heat affected zone (HAZ). The welds resisted strain during forming, forcing the surrounding material to accommodate for the restriction. The failure propagated through the path which had the highest about of strain. For the CP steel, this path was through the BM, perpendicular to the welds. Hole expansion tests (HET) showed that the welds significantly decreased the local formability of the BM. Failure during HET initiated in, and propagated along, the weld HAZ. This was correlated to the microstructures created in the HAZ which were more sensitive to edge stretch failure as compared to the microstructure of the BM. For the DP 980 steel, observations during global formability tests were correlated to the larger soft region within the weld’s HAZ. During forming, strain localized in this zone and caused the material to fail. The failure propagated along the length of the weld which was the path containing the highest about of strain. HET showed that the welds only slightly decreased the local formability of the BM. The failure during HET initiated, and propagated, in the BM rather than the weld. This was correlated to the microstructures created in the HAZ which were less sensitive to edge stretch failure as compared to the microstructure of the BM.
Keywords: laser welding; advanced high strength steel; formability